Mind, culture, and global unrest psychoanalytic reflections - Akhtar, Salman 1946- (Routledge, Taylor & Francis Group, 2018)
In this book the author addresses certain matters of urgent global concern. These include migration across national borders, the current refugee crisis, ethno-racial prejudice, subjective distress of minorities, and, above all, the forever-present ominous shadow of terrorism. Akhtar evolves and advocates a uniquely 'anthropological psychoanalysis' which is a blend of depth psychology and humanities, including sociology, economics, political science, history, and , of course, anthropology. He deconstructs what seems self-evident and confronts his readers with some socio-politically unpleasant realities, both within psychoanalysis and in the prevalent perspectives on the on-going turmoil and bloodshed in today's world
Includes bibliographical references (pages 197-222) and index
Keywords: Religion; Terrorismus; Anthropologie; Psychoanalysis and anthropology; Psychoanalysis and culture